Chemerin as a biomarker at the intersection of inflammation, chemotaxis, coagulation, fibrinolysis and metabolism in resectable non-small cell lung cancer. (November 2018) - Sotiropoulos, George P.; Dalamaga, Maria; Antonakos, Georgios; Marinou, Ioanna; Vogiatzakis, Evaggelos; Kotopouli, Marianna; Karampela, Irene; Christodoulatos, Gerasimos Socrates; Lekka, Antigoni; Papavassiliou, Athanasios G.
Highlights: Circulating chemerin is independently associated with NSCLC risk. Chemerin correlates with metabolic, tumor, inflammatory and hemostatic parameters. Hemostatic parameters are independent predictors of circulating chemerin in NSCLC. Circulating chemerin presents a modest discriminative ability for NSCLC diagnosis. Chemerin is at the intersection of inflammatory, hemostatic and metabolic networks. Abstract: Objectives: Chemerin is an emerging adipocytokine at the intersection of inflammation, chemotaxis, thrombosis, fibrinolysis and metabolism. Our aims were 1) to explore circulating chemerin in resectable non-small cell lung cancer (NSCLC) taking into account its several interfaces; 2) to study its diagnostic potential; and 3) to assess its associations with clinicopathological features of NSCLC. Materials and Methods: In a large case-control study, serum chemerin, insulin resistance and lipid parameters, classic adipocytokines, inflammatory, coagulation, fibrinolysis and tumor biomarkers were determined in 110 consecutive patients with resectable NSCLC and 110 healthy controls matched on age (± 5 years), gender and date of blood draw (± 1 month). Results: NSCLC cases exhibited significantly elevated circulating chemerin compared to controls (p < 0.001). In NSCLC cases, chemerin was positively associated with Homeostasis model assessment score of insulin resistance (HOMA-IR), fibrinogen, plasminogen activity, tumor and inflammatory biomarkers, adiponectin, number of infiltrated lymph nodes and NSCLC stage. In control participants, circulating chemerin was positively correlated with somatometric, metabolic, lipid, hemostatic and inflammatory biomarkers, and leptin. Serum chemerin was independently associated with NSCLC, above and beyond NSCLC risk factors (OR: 2.20, 95% CI: 1.09–4.40, p = 0.03). In cases, hemostatic parameters (platelet count and plasminogen activity), HOMA-IR, CYFRA 21-1, creatinine and plant food consumption emerged as independent predictors of circulating chemerin (p < 0.05). Serum chemerin greater than 220 μg/L (cut-off point) yielded a sensitivity and a specificity of 63% and 91.8% respectively with a modest discriminative ability (AUC = 0.72, 95% C.I. 0.64-0.79) for the diagnosis of NSCLC. Conclusion: Chemerin may represent a potentially useful biomarker in NSCLC integrating tumor-promoting networks, inflammatory and hemostatic mechanisms, and cancer-related metabolic pathways. More preclinical, prospective and longitudinal studies highlighting the pathogenetic role of chemerin in NSCLC are needed to corroborate and extend these data.